2022
DOI: 10.3986/dd.2022.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Začetni tečaj slovenščine in medkulturni dialog pri vključevanju otrok priseljencev

Abstract: Prenovljena osnovno- in srednješolska zakonodaja predvideva intenzivni začetni tečaj slovenščine ter individualno spremljanje napredka vključevanja. Na voljo je vedno več didaktičnega gradiva za različno starostno stopnjo otrok, a izzivi ostajajo. Še več jih je pri izvajanju medkulturnega dialoga v okviru pouka. Učni načrti in učna gradiva bi morali odsevati družbeno raznolikost, a so priseljenke in priseljenci, pripadnice in pripadniki manjšin v njih največkrat nevidni ali prikazani pristransko. To je treba s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
4
0
7
Order By: Relevance
“…On the contrary, Slovenia, a post-socialist country, obtained high results regarding indicators associated with methods of intercultural education (especially school language policy) despite its limited experience with (school) integration of migrant adolescents. This lack of experience is often expressed by inadequate and inappropriate educational approaches that were criticized in other studies (see for example Rutar, 2018;Dežan and Sedmak 2020;Medarić et al, 2021;Vižintin and Kern, 2022). These authors concluded that primary and secondary schools in Slovenia still have a long way to implement intercultural dialogue in pedagogical activities thoroughly, however, our findings signalize turn for the better.…”
Section: Discussionmentioning
confidence: 49%
“…On the contrary, Slovenia, a post-socialist country, obtained high results regarding indicators associated with methods of intercultural education (especially school language policy) despite its limited experience with (school) integration of migrant adolescents. This lack of experience is often expressed by inadequate and inappropriate educational approaches that were criticized in other studies (see for example Rutar, 2018;Dežan and Sedmak 2020;Medarić et al, 2021;Vižintin and Kern, 2022). These authors concluded that primary and secondary schools in Slovenia still have a long way to implement intercultural dialogue in pedagogical activities thoroughly, however, our findings signalize turn for the better.…”
Section: Discussionmentioning
confidence: 49%
“…In the Slovenian context, only one paper deals with the professional re-integration of international teachers into the school system. Marijanca Ajša Vižintin (2009) describes a project which, besides teaching Slovene as a second/foreign language, introduced teaching of the language of origin (Macedonian and Albanian) and the cultures of immigrant children in Slovenia. The teaching was presented from the perspective of three international teachers who immigrated to Slovenia, two from Albania and one from Macedonia, and their integration in the specific school setting.…”
Section: Results and Findings Of The Conducted Empirical Research -A ...mentioning
confidence: 99%
“…Nevertheless, intercultural education has gained more attention in recent decades, mainly through European initiatives that have resulted in several documents addressing the issue of interculturality and integration of migrant children in Slovenian schools. However, these mostly take the form of guidelines, and there is still a lack of comprehensive policy solution as often pointed out by experts and researchers in the field (see Grobelšek, 2010;Razpotnik, 2011;Sedmak et al, 2020;Skubic Ermec, 2006;Vižintin, 2014Vižintin, , 2018. As Peček Čuk and Skubic Ermenc (2016) critically state, interculturality in Slovenia is currently limited to 'providing additional learning of Slovene, additional learning of the other mother tongues and the provision of individual intercultural activities and lessons' (Peček Čuk & Skubic Ermenc, 2016, p. 21).…”
Section: The Role Of Schools In the Integration Of Migrant Children A...mentioning
confidence: 99%
“…No obstante, la educación intercultural ha atraído mayor atención en las últimas décadas, principalmente a través de iniciativas europeas que produjeron diversos documentos en los que se aborda la interculturalidad y la integración de los niños migrantes en las escuelas eslovenas. Sin embargo, la mayoría de estos documentos adoptan la forma de directrices, y todavía es necesaria una solución política global como suelen indicar los expertos e investigadores en este ámbito (véase Grobelšek, 2010;Razpotnik, 2011;Sedmak et al, 2020;Skubic Ermec, 2006;Vižintin, 2014Vižintin, , 2018. Como Peček Čuk y Skubic Ermenc (2016) apuntan en su estudio crítico, en la Eslovenia actual, la interculturalidad se limita a 'ofrecer el aprendizaje de la lengua eslovena, el aprendizaje adicional de las lenguas maternas y actividades y lecciones interculturales individuales' (Peček Čuk & Skubic Ermenc, 2016, p. 21).…”
Section: El Papel De Las Escuelas En La Integración De Niños Migrante...unclassified
See 1 more Smart Citation